Analysis of the Contribution of Intellectual Capital to Economic Growth Based on an Empirical Analysis of Prefecture-Level Cities in Guangxi. (9th July 2021) - Zeng, Qun; Tan, ZhenHai; Liu, Chunnian
Abstract : The purpose of this paper is to explore the reasons for the differences in intellectual capital between regions and put forward reasonable suggestions for regional economic development through the use of an intellectual capital measurement model. Based on a sample of 14 cities in Guangxi in 2017, this work builds a set of indicator systems to evaluate intellectual capital contributions. First, the comprehensive intellectual capital score of each region is calculated, and the principal component analysis is used to analyze three elements. Second, a regression equation model between the regional intellectual capital and the regional economic status indicator—GDP—is established, and a descriptive statistical test, a correlation test, and a robustness test are carried out on the model. This work finds that the three major factors of regional intellectual capital have positive effects on the level of regional economic development, among which the contribution of regional structural capital to economic development is the largest, reaching more than 50%, followed by human capital, and, finally, relational capital. The unbalanced characteristics of intellectual capital between cities are quite prominent, and thus, the alleviation of the unbalanced development of cities has become a problem that must be urgently addressed. Structural capital has the highest impact on GDP of all types of capital, with government income from structural capital accounting for more than half of total incomes.